Adsorption of Zn from aqueous solution by activated carbon derived empty fruit bunches: Statistical approach - Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Qudsieh, Isam Y.; Kabbashi, Nassereldeen Ahmed; Al-Mamun, Abdullah; Kamaldin, Noraini (2009)
Oil palm (OP) industry in Malaysia produces about 40 million tones of oil palm biomass containing empty fruit bunches (EFB), trunks, fronds, fiber and fruit shell. The EFB represents about 10% of the total by-products generated which is either left in the plantation to provide organic nutrients to trees or burned illegally. Therefore a promising and comparatively new approach for the production of activated carbon from EFB for removal of Zn from aqueous solution was carried out in laboratory. Cost effectiveness, availability and adsorptive properties are the main criteria for choosing the adsorbent (activated carbon) to remove heavy metals from wastewater. Considering these criteria many researchers have investigated activated carbons production from agricultural by-products and other wastes such as rice husk, rice straw, sugarcane bagasse, oil palm stone, olive waste cake, sewage sludge, paper mill sludge and municipal waste for different application especially industrial wastewater treatment. The abundant oil palm industrial waste empty fruit bunches (EFB) generated locally were considered to produce activated carbon for the adsorption of Zn from aqueous solution. Thermal activation temperature (10000C) and time (30 min) were optimized to produce activated carbon from EFB. The effect of agitation rate, contact time, initial concentration of adsorbate, adsorbent dose and pH were observed to optimize the adsorption process. A statistical optimization was conducted by using central composite design (CDD) under response surface methodology (RSM) with five factors. The experimental data were analyzed using a statistical software MINITAB Release 14 to develop the polynomial regression model for determining the optimum conditions. The results indicated that the optimum conditions for maximum adsorption of Zn were (6 mg/g): agitation rate of 100 rpm, contact time of 2.5 hrs, initial adsorbate concentration of 12.5 mg/L, adsorbent dose of 2 g/L and pH of 4. Adsorption isotherms and kinetics studies were conducted to evaluate biosorption process. Removal of Zn compounds by the activated carbon derived from EFB was found to be favorable and hence, activated carbon could be considered as alternatives to commercial absorbents for the treatment of Zn containing industrial wastewater as well as any other effluents that contain heavy metals and organic substances.